6(-2+7x)+4x=36-2x

Simple and best practice solution for 6(-2+7x)+4x=36-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(-2+7x)+4x=36-2x equation:


Simplifying
6(-2 + 7x) + 4x = 36 + -2x
(-2 * 6 + 7x * 6) + 4x = 36 + -2x
(-12 + 42x) + 4x = 36 + -2x

Combine like terms: 42x + 4x = 46x
-12 + 46x = 36 + -2x

Solving
-12 + 46x = 36 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-12 + 46x + 2x = 36 + -2x + 2x

Combine like terms: 46x + 2x = 48x
-12 + 48x = 36 + -2x + 2x

Combine like terms: -2x + 2x = 0
-12 + 48x = 36 + 0
-12 + 48x = 36

Add '12' to each side of the equation.
-12 + 12 + 48x = 36 + 12

Combine like terms: -12 + 12 = 0
0 + 48x = 36 + 12
48x = 36 + 12

Combine like terms: 36 + 12 = 48
48x = 48

Divide each side by '48'.
x = 1

Simplifying
x = 1

See similar equations:

| 2(2.5x-5)+2= | | -8a+10=-8(a+3) | | n=-3/8=1/8 | | 2+(5+y)=0 | | 9(-8-2p)= | | -4+8(p+4)=4(4p-1) | | 15-9/3=-9 | | 14x-14=16x | | 10-3a=40 | | 81[(5+3)-5]= | | Y^2-9y=-18 | | 4t+9= | | -4(5-4x)=-40+6x | | -7=a-7 | | 7(m-7)=28-4m | | 33-3n=-6(n-8) | | -17=15n-20 | | 11m+10=9m | | 60=log(x) | | 4=4x+9 | | -3(n-4)-3=3-(n+2) | | 7x+1=1+8x | | ab+5a-b-5=0 | | 18(v+3)-2v=4(4v+1)-11 | | 6/5:2,7 | | 4=p-36 | | -7+8p=-7-2p | | 8v-(8v-6)= | | -12-5y=-32 | | √25/289 | | 6x2/3x | | 5/6=1/2v |

Equations solver categories